2020
DOI: 10.3389/fendo.2020.536100
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Serum Delta FSH Level and Ovarian Response in IVF/ICSI Cycles

Abstract: Background: When ovarian response to FSH stimulation for IVF/ICSI is unsatisfactory, the FSH dose is often adjusted in the treatment cycles, thereby assuming that hormone status and follicular development were insufficient for optimal stimulation. Objectives: To evaluate whether serum delta FSH levels between D6 of gonadotrophin use and basal serum FSH or between D6 of gonadotrophin use and D1 of gonadotrophin use predict ovarian response in IVF/ICSI cycles. Method: The participants of this retrospective study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…As shown, the markers standing for the ovarian response differed significantly between two groups. Superior responders had a significantly higher AMH compared to inappropriate responders [4.59 (3.05, 6.8) vs 2.19 (1.52, 3.53), p = 0.000], a significantly higher AFC [17 (14, 20) vs 12 (9,16), p = 0.000], but a significantly lower basal FSH [6.08 (5.27, 6.92) vs 6.78 (5.69, 7.70), p = 0.002]. There was no difference in serum FSH levels on the gonadotrophin starting day between two groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown, the markers standing for the ovarian response differed significantly between two groups. Superior responders had a significantly higher AMH compared to inappropriate responders [4.59 (3.05, 6.8) vs 2.19 (1.52, 3.53), p = 0.000], a significantly higher AFC [17 (14, 20) vs 12 (9,16), p = 0.000], but a significantly lower basal FSH [6.08 (5.27, 6.92) vs 6.78 (5.69, 7.70), p = 0.002]. There was no difference in serum FSH levels on the gonadotrophin starting day between two groups.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we identified that serum sFSH levels had significantly distinction between different ovarian responders undergoing the IVF/ICSI cycles in GnRH agonist cycles. A recent similar study [16] concluded that there was a weak relationship between ovarian response and serum delta FSH levels (the difference between serum FSH level on D6 of gonadotropin (Gn) use and basal serum FSH level) in the rFSH fixed dose treatment protocol. Because the study only focused on the comparison between the discrepancy of FSH level and ovarian response, it is difficult to directly compare these results to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen levels in females would be reduced as the decline of ovarian reserve, resulting in an increase of FSH secretion. The elevated basal FSH (bFSH) level is associated with the declined ovarian reserve ( 33 ). Therefore, bFSH has been widely used in reproductive medicine to evaluate the ovarian reserve and its response.…”
Section: Discussionmentioning
confidence: 99%
“…After the age of 35, the number of follicles decreases sharply, probably due to the incidence of chromosomal defects increases, and the sensitivity of granulosa cells to gonadotropin decreases. Some studies suggested that serum FSH increases significantly when ovarian reserve is severely declined and fluctuates significantly during the menstrual cycle; therefore, FSH has no optimal sensitivity or specificity in predicting ovarian response ( 16 ). Our data indicated that FSH was associated with ovarian response, but it shouldn’t be single-used as the predictor due to its defects.…”
Section: Discussionmentioning
confidence: 99%